The balancing of empowerment. A strategic resource based model of organizing innovation activities in service and low-tech firms - Sundbo, Jon (Technovation)
The writer focuses on balancing the empowerment of employees to promote corporate entrepreneurship with appropriate control measures. Networking and the empowerment of customers are felt to be under utilized, whilst strategy and a linear organization of innovation are considered most important as control mechanisms.